2020
DOI: 10.1101/2020.11.09.375501
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Estimation of non-additive genetic variance in human complex traits from a large sample of unrelated individuals

Abstract: Non-additive genetic variance for complex traits is traditionally estimated from data on relatives. It is notoriously difficult to estimate without bias in non-laboratory species, including humans, because of possible confounding with environmental covariance among relatives. In principle, non-additive variance attributable to common DNA variants can be estimated from a random sample of unrelated individuals with genome-wide SNP data. Here, we jointly estimate the proportion of variance explained by additive ,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 48 publications
2
11
0
Order By: Relevance
“…Fourth, although we have shown that our approach is robust to certain types of model misspecification (e.g., effect sizes drawn from mixture of normal distributions, imperfect tagging of causal effects), we do not exclude the possibility of nonlinear interaction effects such as GxE, GxG and dominance effects [55][56][57][58] . We also assume that phenotypes are normally distributed or can be properly quantile normalized.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, although we have shown that our approach is robust to certain types of model misspecification (e.g., effect sizes drawn from mixture of normal distributions, imperfect tagging of causal effects), we do not exclude the possibility of nonlinear interaction effects such as GxE, GxG and dominance effects [55][56][57][58] . We also assume that phenotypes are normally distributed or can be properly quantile normalized.…”
Section: Discussionmentioning
confidence: 99%
“…However, the increase in power is still expected to be substantial from additive components that are usually considered major in a genetic architecture, with effect sizes highly similar across populations (Wojcik et al, 2019). Additionally, currently the contribution from epistasis or G × E components to most trait variability is estimated to be relatively small (Wang et al, 2019; Dahl et al, 2020; Hivert et al, 2020). For variants with heterogeneous effect sizes per ancestry, other local ancestry-aware regression methods could potentially improve the power of detection in admixed populations (Atkinson et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Behravan and colleagues also reported that, by allowing nonparametric interactions between genetic and demographic factors, the AI models improved the mean average precision in breast cancer prediction from 0.74 to 0.78, comparing with the ones using SNPs alone (22). Despite promising data regarding AI-based methods, caution is warranted as the contribution of epistatic effects over and beyond additive effects may be small for complex traits, like breast cancer (23).…”
Section: Is It Time To Move Beyond Predictive Models?mentioning
confidence: 99%